A Polarity Reversion Elimination Method for LTE-Advanced Frequency Offset Estimation - Guoqing Jia; Shanji Chen; Chao Chen; Xiaohong Ji; Weidong Fang (Dianxin kexue)
Traditional fractional frequency offset（FFO）estimation algorithm pay less attention to FFO polarity estimation.Noise and channel fading induced FFO estimation polarity reversion degrades the frequency synchronization performance inevitably.An efficient FFO polarity detection method was proposed in LTE-Advanced system to solve the problem，which utilized the mirror symmetry property of time-domain primary synchronization signal（PSS）.Numerical results show that the proposed method can depress FFO polarity reversion efficiently.